Rethinking sexuality - Richardson, Diane (SAGE, 2000)
This thoughtful and accessible book provides a critical examination of the central debates attached to conceptualizing sexuality as a site of knowledge and politics. These are explored in chapters on the meaning of heterosexuality, sexual citizenship and the associated notions of sexual rights and obligations, queer theory and its relationship with feminisms, both `new' and `old'. Also included is discussion of responses to the HIV/AIDS epidemic and the implications for understandings of gender and sexuality.